Key concepts for the new model of social policy of the Republic of Kazakhstan (Journal of Philosophy Culture and Political Science, 2022)
Abstract. The article discusses a number of ideological and conceptual and methodological issues related to the development of a new model of social policy of the Republic of Kazakhstan. The introduction reveals the relevance of the topic of the article through an appeal to a number of fundamental provisions formulated by the head of state K.K. Tokaev in his speech at a meeting of the Mazhilis of the Parliament of the Republic of Kazakhstan on January 11, 2022. The first section substantiates the thesis that an integral criterion for the effectiveness of the social policy of the state is to improve the quality of life of the country's population. It is concluded that in monitoring the quality of life it is equally necessary to identify both subjective assessments and objective parameters of the material and spiritual spheres of social life. In the second section, a normative and descriptive axiology of the concept of "good society" is built. Its difference from the utopian concepts of the "ideal society" is revealed. The third section reveals the dialectics of the relationship between the right and the social state. In conclusion, the conclusions of the study are formulated. The main conclusion is that improving the quality of life of the bulk of the population, the creation of a "good society" and the formation of a social legal state is a triune task of a new stage of the social policy of the Republic of Kazakhstan. Its solution should become a strategic priority for the comprehensive modernization of Kazakhstani society.Key words: social policy, quality of life, good society, rule of law, welfare state.